Development and Performance Evaluation of Light Shelves Using Width-Adjustable Reflectors. (1st April 2018) - Lee, Heangwoo; Park, Seonghyun; Seo, Janghoo
Abstract : In recent years, there has been an increase in the consumption of energy for lighting purposes, which has led to an increase in the number of studies being conducted on this subject. Most studies have focused on light shelves, which are daylighting systems used for reducing the lighting energy required for the interiors of buildings. However, the existing light shelves cannot actively deal with external environmental factors, which often lead to an infringement of the right to light during the night when the performance of the light shelf deteriorates. Therefore, in this study, we propose a light shelf with a width-adjustable reflector and verify its validity using a testbed. The reflector of the proposed light shelf system is modularized so that the length can be adjusted in stages. The optimum width of the light shelf is calculated in terms of the energy reduction and uniformity ratio improvement, and the obtained optimum width is varied depending on the season. We find that the width-adjustable reflector can save 20% and 21.6% more lighting energy than light shelves with fixed reflector widths of 0.3 m and 0.6 m, respectively.